Permasalahan Pendidikan Anak Pesisir: Studi Kasus di Dusun Taipa Kabupaten Takalar - khaeruddin; Ulul Azmi Mustari; Feri Padli (Arus Jurnal Pendidikan, 2022)
Abstract: This research is motivated by general problems that occur in the education system of coastal communities, so this study aims to describe the problems contained in the education of coastal children. This study will focus on examining the educational problems experienced by coastal children in Taipa Hamlet, using direct observation research methods, with a qualitative descriptive approach. Based on the findings in the field, there are several problems experienced by coastal children in Taipa Hamlet in receiving education, namely inadequate facilities, lack of support from parents, and low interest in learning for coastal children in Taipa Hamlet. The elementary schools in Taipa Hamlet are good, although there are still some classrooms that are not good. The lack of educators, as well as the lack of educational socialization in coastal communities so that lack of education is considered less important in life, causes a lack of parental support in the learning process of their children. Lack of support from parents is also a crucial problem, because children do not get support from their parents. or paying attention to their education will greatly impact their interest in learning. This is because their parents think that education is not too important, the important thing is to make money by helping their family's economy.